ANÁLISE DE ESCAMAS DE PEIXES PARA MONITORAMENTO AMBIENTAL POR ESPECTROSCOPIA DE PLASMAINDUZIDA POR LASER (LIBS) - DA COSTA SHIMADA, Julia Thiemy,; SOUZA, Bianca de Andrade,; ANDRADE, Luis Humberto da Cunha,; LIMA JÚNIOR, Sidnei Eduardo, (ANAIS DO ENIC, 2024)
-